Effectiveness of Intravitreal Bevacizumab for Diabetic Macular Edema in Eyes with Preserved Visual Acuity: A Prospective Clinical Trial - Daryabari, Seyed Hashem; Hassani , Mahmood; Alishiri , Aliagha (Journal of Ophthalmic and Optometric Sciences, 2024)
Purpose: To assess the effectiveness of intravitreal Bevacizumab injections in reducing central macular thickness and preserving visual acuity in diabetic patients with center-involving macular edema and good baseline vision. Patients and Methods: This prospective clinical trial was conducted over 18 months starting in April 2017. Patients with non-proliferative diabetic retinopathy, visual acuity ≥20/25, and central macular thickness > 300 µm on OCT were included. Participants were assigned to two groups: one received intravitreal Bevacizumab (1.2 mg), and the other was monitored without treatment. Central macular thickness and best-corrected visual acuity were measured at baseline and six months postoperatively. Results: Twenty-two eyes completed the study (12 treated, 10 control). In the treatment group, the mean macular thickness decreased from 319 µm to 301 µm (P = 0.031). In the control group, it increased from 318 µm to 328 µm. However, the intergroup difference at six months was not statistically significant (P = 0.581). Visual acuity declined slightly in both groups: from 9.05/10 to 8.7/10 in the treated group and from 9.3/10 to 9.2/10 in controls, with no significant difference between groups (P = 0.373). No adverse events were reported. Conclusion: Bevacizumab injections led to a modest reduction in macular thickness but did not significantly improve or preserve visual acuity in diabetic patients with good baseline vision. These findings suggest that factors beyond vascular endothelial growth factor may play a role in early-stage diabetic macular edema. Further studies with a higher sample size are suggested to confirm our findings.